Building Bridges from the Decoding Interview to Teaching Practice. (June 2017) - Pettit, Jennifer; Rathburn, Melanie; Calvert, Victoria; Lexier, Roberta; Underwood, Margot; Gleeson, Judy; Dean, Yasmin
Abstract : This chapter describes a multidisciplinary faculty self‐study about reciprocity in service‐learning. The study began with each coauthor participating in a Decoding interview. We describe how Decoding combined with collaborative self‐study had a positive impact on our teaching practice.